Illumination of parameter contributions on uneven break phenomenon in underground stoping mines - Jang, Hyong Doo; Topal, Erkan; Kawamura, Y. (Elsevier, 2016)
© 2016 Published by Elsevier B.V. on behalf of China University of Mining & Technology.